Integrated Functions of Pax3 and Pax7 in the Regulation of Proliferation, Cell Size and Myogenic Differentiation - Collins, Charlotte A.; Gnocchi, Viola F.; White, Robert B.; Boldrin, Luisa; Perez-Ruiz, Ana; Relaix, Frederic; Morgan, Jennifer E.; Zammit, Peter S. (PLOS ONE, 2009)
Pax3 and Pax7 are paired-box transcription factors with roles in developmental and adult regenerative myogenesis. Pax3 and Pax7 are expressed by postnatal satellite cells or their progeny but are down regulated during myogenic differentiation. We now show that constitutive expression of Pax3 or Pax7 in either satellite cells or C2C12 myoblasts results in an increased proliferative rate and decreased cell size. Conversely, expression of dominant-negative constructs leads to slowing of cell division, a dramatic increase in cell size and altered morphology. Similarly to the effects of Pax7, retroviral expression of Pax3 increases levels of Myf5 mRNA and MyoD protein, but does not result in sustained inhibition of myogenic differentiation. However, expression of Pax3 or Pax7 dominant-negative constructs inhibits expression of Myf5, MyoD and myogenin, and prevents differentiation from proceeding. In fibroblasts, expression of Pax3 or Pax7, or dominant-negative inhibition of these factors, reproduce the effects on cell size, morphology and proliferation seen in myoblasts. Our results show that in muscle progenitor cells, Pax3 and Pax7 function to maintain expression of myogenic regulatory factors, and promote population expansion, but are also required for myogenic differentiation to proceed.